On the interaction between self-excited and forced oscillations - Cau, Thai Manh; Khang, Nguyen Van (Vietnam Journal of Mechanics, 2002)
The influence of the exciting force to resonant characteristics in a model of the small oscillation is investigated. Averaging method is used to determine resonant stationary solutions of all possible resonant oscillations and their stability. The numerical simulations used for oscillations in time domain and the analytic approaches give consistent results.